Sejarah Karya-Karya Intelektual Muslim dan Pranata/Lembaga Sosial - Maulana, Indra Maulana Indra (Journal of Indonesian History, 2023)
This article explains the history of intellectual works produced by the Muslim community throughout the centuries and their relationship to social institutions or institutions in Islamic civilization. The main focus of the research is to reveal how Muslim intellectual thought has made a significant contribution to the development of social institutions in various historical contexts. This article includes an analysis of intellectual works related to law, ethics, education, and social order, and identifies their impact on Muslim society. Through a comprehensive literature review, this article examines the development of intellectualism in the Islamic tradition from early times to the modern era. Additionally, this article highlights the role of famous figures in the history of Islamic thought and the way their concepts have shaped social institutions such as the sharia legal system, educational institutions, and the social structure of Muslim societies. This research also highlights the contribution of Muslim intellectuals to the development of science and technology, which in turn influences social institutions and the development of civilization in the Islamic world. Through a deeper understanding of the history of Muslim intellectual works, this article aims to provide insight into how intellectualism and social institutions are interrelated in the context of Islamic civilization. In conclusion, this article considers the important role of Muslim intellectual works in shaping social institutions and institutions in the Islamic world throughout its history. Understanding this relationship can provide a better perspective on how Islamic intellectualism played a role in directing social, legal, and ethical developments in Muslim civilization. Keywords: Muslim Intellectuals, Muslim Intellectual Works.